2021
DOI: 10.1002/ep.13621
|View full text |Cite
|
Sign up to set email alerts
|

The nexus between environmental degradation and industrial development in Pakistan and roles of financial development and fossil fuel

Abstract: The swift escalation in the emission of greenhouse gases (GHG) has gained universal concern and on the global scale it has gotten the attention of research scholars and policy advisers. The use of fossil fuel in industrial and domestic activities has been labeled as a key cause for the production of GHG in the environment; in the mean-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…This EKC hypothesis was further validated by the interaction between infrastructure investment in the transportation system and environmental degradation of 21 OECD countries (Erdogan, 2020). Elsewhere, the dynamic link between Pakistan's CO 2 emissions and industrial development was examined for effectiveness, with the variables found to be co-integrated, involving both long-and short-term dynamics that validate the hypothesis (Ali et al, 2021).…”
Section: Relationship Between Industrial Pollution and Economic Growthmentioning
confidence: 88%
“…This EKC hypothesis was further validated by the interaction between infrastructure investment in the transportation system and environmental degradation of 21 OECD countries (Erdogan, 2020). Elsewhere, the dynamic link between Pakistan's CO 2 emissions and industrial development was examined for effectiveness, with the variables found to be co-integrated, involving both long-and short-term dynamics that validate the hypothesis (Ali et al, 2021).…”
Section: Relationship Between Industrial Pollution and Economic Growthmentioning
confidence: 88%
“…Correspondingly, Baek (2015) reported that there were weak evidences of the EKC relationship in Arctic countries. Ali et al (2021) investigated the validity of a dynamic connection between CO 2 and industrial growth employing ARDL model methods with structural breaks cointegration to capture the impact of fossil fuel consumption and economic growth on CO 2 emissions. All relevant factors were found to be cointegrated, and the long-term and short-term trends demonstrated the validity of the EKC hypothesis's inverted U -shaped connection between industrial growth and CO 2 , as founded by the Lind and Mehlum test.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering the both trade openness, industrial development and construction as independent variables in terms of testing the EKC hypothesis, there is no works by using two variables together. However, if those variables considered separately as independent variables, there are some researches (Adedoyin et al, 2022;Ali, et al, 2021;Li and Haneklaus, 2022;Zhou, et al, 2021) in the academic literature. While generating this part, besides examining the most recent work, researches on different economies are considered as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although high-income countries are sensitive to environmental enhancement, it has been observed that insensitivity is high in middle and low-income countries. In addition, it is found that the increase in trade openness and per capita income negatively affected CO 2 emissions.When the subject is considered in terms of the relationship between industrial development and the EKC hypothesis,Ali et al (2021) perform ARDL model through structural breaks co-integration test to examine the existence of a dynamic relationship between industrial development and CO 2 by capturing the impact of fossil fuel usage and economic growth on Carbon emission. All variables have been discovered to be co-integrated and the short-run and long-run dynamics have demonstrated the existence of inverted U-shaped of the EKC hypothesis where there has been inverted U-shaped association between carbon emission and industrial development which had been established by Lind and Mehlum test as well.…”
mentioning
confidence: 99%